2019
DOI: 10.1002/pca.2834
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative1HNMR spectroscopy for the determination of oxyresveratrol inArtocarpus lacuchaheartwood

Abstract: Introduction Quantitative nuclear magnetic resonance (qNMR) spectroscopy is an analytical method based on the principles of NMR spectroscopy. The main advantages of this method are its simplicity, time efficiency, high accuracy and reproducibility, and it is a non‐destructive technique. Objective To evaluate and standardise the quality of Artocarpus lacucha heartwood. A method for quantifying its oxyresveratrol content using qNMR was developed. Methodology Proton (1H)NMR (400 MHz) spectroscopy was used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The physical constants and spectroscopic properties (particularly NMR data) of both natural and synthetic ORV are presented in numerous reports [ 14 , 21 , 34 , 42 , 49 , 56 , 57 , 72 , 76 , 107 , 128 ]. The data for the crystal structure of ORV in the form of dihydrate are also available [ 129 ].…”
Section: Natural Sourcesmentioning
confidence: 99%
“…The physical constants and spectroscopic properties (particularly NMR data) of both natural and synthetic ORV are presented in numerous reports [ 14 , 21 , 34 , 42 , 49 , 56 , 57 , 72 , 76 , 107 , 128 ]. The data for the crystal structure of ORV in the form of dihydrate are also available [ 129 ].…”
Section: Natural Sourcesmentioning
confidence: 99%
“…Sinensis). At present, some studies have reported various of novel methods of medicinal plants identi cation, such as barcode-based melting curve analysis, DNA labeling or 1 HNMR metabolite ngerprinting and so on 26,27 . Although these methods can accurately identify species, they require specialized knowledge, statistical analysis, and complex instruments.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear magnetic resonance (NMR) technique can detect a large number of components simultaneously in complex mixtures. In addition, sample preparation for NMR spectroscopy is simpler and less time consuming than for chromatography [18][19][20]. The purpose of this work is to provide a simple and fast procedure to determine acrolein in cider by proton nuclear magnetic resonance ( 1 H NMR), in the same way that our research group has already achieved with other analytes, for example, caffeine, trigonelline, formic acid, and 5-(hydroxymethyl)furfural in soluble coffees [21].…”
Section: Introductionmentioning
confidence: 99%